Pretreatment of Achnatherum splendens by Soaking in Aqueous Ammonia - Jun, Ren; Ling, Tao; Tianri, Ni; Jianxiu, Hao; Yamei, Gao (Asian Journal of Chemistry, 2011)
Soaking in aqueous ammonia was investigated as a pretreatment method for Achnatherum splendens. The method involves batch treatment of feedstock with aqueous ammonia (5-25 wt %) at 45-85 ºC for 12-72 h. It was found that ammonia concentration, reaction temperature and reaction time all had significant effects on delignification. These factors also had significant effects on the lignin, hemicellulose and cellulose contents of soaking in aqueous ammoniatreated solids. Optimum conditions were obtained as follows: 10 wt % of ammonia, temperature 55 ºC, 36 h of reaction time and 12:1 (based on wt) of liquid-to-solid ratio. Under these conditions, delignification reached to 26.58 % and the content of cellulose in pretreated solids increased to 64.20% while the content of hemicellulose decreased to 23.63 %.